Selective Killing Effects of Cold Atmospheric Pressure Plasma with NO Induced Dysfunction of Epidermal Growth Factor Receptor in Oral Squamous Cell Carcinoma - Jung‐Hwan Lee; Ji-Yeon Om; Yong‐Hee Kim; Kwang‐Mahn Kim; Eun Ha Choi; Kyoung Nam Kim (2016)
The aim of this study is to investigate the effects of cold atmospheric pressure plasma (CAP)-induced radicals on the epidermal growth factor receptor (EGFR), which is overexpressed by oral squamous cell carcinoma, to determine the underlying mechanism of selective killing. CAP-induced highly reactive radicals were observed in both plasma plume and cell culture media. The selective killing effect was observed in oral squamous cell carcinoma compared with normal human gingival fibroblast. Degradation and dysfunction of EGFRs were observed only in the EGFR-overexpressing oral squamous cell carcinoma and not in the normal cell. Nitric oxide scavenger pretreatment in cell culture media before CAP treatment rescued above degradation and dysfunction of the EGFR as well as the killing effect in oral squamous cell carcinoma. CAP may be a promising cancer treatment method by inducing EGFR dysfunction in EGFR-overexpressing oral squamous cell carcinoma via nitric oxide radicals.